Growth factors regulate phototransduction in retinal rods by modulating cyclic nucleotide-gated channels through dephosphorylation of a specific tyrosine residue - Savchenko, Alexei (The National Academy of Sciences, 2001)
Illumination of vertebrate rod photoreceptors leads to a decrease in the cytoplasmic cGMP concentration and closure of cyclic nucleotide-gated (CNG) channels. Except for Ca(2+), which plays a negative feedback role in adaptation, and 11-cis-retinal, supplied by the retinal pigment epithelium, all of the biochemical machinery of phototransduction is thought to be contained within rod outer segments without involvement of extrinsic regulatory molecules. Here we show that insulin-like growth factor-I (IGF-I), a paracrine factor released from the retinal pigment epithelium, alters phototransduction by rapidly increasing the cGMP sensitivity of CNG channels. The IGF-I-signaling pathway ultimately involves a protein tyrosine phosphatase that catalyzes dephosphorylation of a specific residue in the α-subunit of the rod CNG channel protein. IGF-I conjointly accelerates the kinetics and increases the amplitude of the light response, distinct from events that accompany adaptation. These effects of IGF-I could result from the enhancement of the cGMP sensitivity of CNG channels. Hence, in addition to long-term control of development and survival of rods, growth factors regulate phototransduction in the short term by modulating CNG channels.